SIMULASI TEKNIK POWER CONTROL DAN MULTI USER DETECTION PADA SISTEM KOMUNIKASI DS-CDMA - Yuli Christyono (TEKNIK, 2010)
CDMA is interference limited multiple access system. Because all users transmit on the same frequency,internal interference generated by the system is the most significant factor in determining system capacity andcall quality. The transmit power for each user must be reduced to limit interference, however, the power shouldbe enough to maintain the required Eb/No (signal to noise ratio) for a satisfactory call quality. Maximumcapacity is achieved when Eb/No of every user is at the minimum level needed for the acceptable channelperformance. As the MS moves around, the RF environment continuously changes due to fast and slow fading,external interference, shadowing , and other factors. The aim of the dynamic power control is to limittransmitted power on both the links while maintaining link quality under all conditions. Additional advantagesare longer mobile battery life and longer life span of BTS power amplifiers.In this research will be made a sumulation of power control and multi user detection to avoid the interferencebetween MS.Observations show that the increasing number of users will decrease the value of Signal to Interfrence Ratio(SIR) / SIR below the target. To cope the growing number of users increases can be done by iteration / updatingpower transmit so the convergence computation can be reached and target value SIR can be achieved. Inaddition, to reduce interference can also be done by extending the number of chips.